Reviews and Responses for Evaluating Potential Fuel-Savings of External Alternative Ground Propulsion Systems - Waltert, Manuel; Figuet, Benoit; Felux, Michael; Olive, Xavier; Strohmeier, Martin; Polishchuk, Tatiana (Journal of Open Aviation Science, 2025)
See detailed reviews and responses in the PDF file. DOI for the original paper: https://doi.org/10.59490/joas.2024.7888